POLITIK LUAR NEGERI INDONESIA DAN LINGKUNGAN HIDUP - Wuryandari, Ganewati (Pusat Penelitian Politik, 2011)
Environmental issue has become an important topic in today s internationalpolitical dynamics Environmentaldegradation cause byphenomenon ofglobal warming and climate change has become a serious globalproblem Inthe future the continuing of the problems may befar reaching impact on sustainability of the lives and survivalofall people in the world Therefore the environment issues is supposed to be reflected in state policy which noexception in Indonesia sforeign policy International cooperation is a rational solutionforfinding the way out oftheexisting environmentalproblems In the terms of cooperation states which represented by government is not only thedriving actors in the stage but there are other actors such as NGOs international organizations and multinationalcompanies MNCs that take part in managing the environmental crisis This study examines Indonesian foreignpolicy in addressing environmental issues especially global warming and climate change This studyfocuses itstime limitfrom 1972 until 2009 This study is qualitative research with its data is obtained through literature andfield research The result ofthis study shows that although Indonesian government shows its commitment to environmental issues in theforeignpolicy this study underlines the contradiction between rhetoric and implementationThis contradiction reflects dilemma ofrealism and idealism in Indonesiaforeign policy